Double-blind comparison of tolamolol, propranolol, practolol, and placebo in the treatment of angina pectoris. Issue 5960 (29th March 1975) - Jackson, G; Atkinson, L; Oram, S
Abstract : Forty-two patients with angina pectoris have completed a randomized, double-blind trial comparing tolamolol 100 mg and 200 mg with propranolol 80 mg, practolol 100 mg, and placebo, all given three times a day. Tolamolol 200 mg thrice daily was found to be equivalent to propranolol 80 mg thrice daily in anti-anginal efficacy. Anginal attack rates and trinitrin consumption were significantly reduced by all active treatments as compared with the placebo but tolamolol and propranolol were the most effective. Tolamolol 200 mg thrice daily was most effective in reducing blood pressure, while propranolol was most effective in reducing the resting heart rate. All treatments except the placebo significantly increased the amount of exercise which could be performed before angina appeared (exercise work), while tolamolol 200 mg thrice daily significantly reduced Robinson's index when compared with all other active agents. The degree of S-T segment depression induced by exercise was significantly lessened by both tolamolol and propranolol but not by practolol or placebo. There was no difference in patient preference between tolamolol and propranolol but tolamolol at both dose levels was preferred to practolol. Both tolamolol and propranolol are potent adrenergic beta-receptor antagonists and equal in anti-anginal efficacy but tolamolol has the advantage of being cardioselective. It is superior to practolol.